Long-term efficacy of an inactivated H5N1 whole-particle influenza vaccine in nonhuman primates - Misako Nakayama; Naoko Kitagawa; Cong Thanh Nguyen; Takako Sasamura; Kyoko Takashima; Hirohito Ishigaki; Hideaki Ishida; Saori Suzuki; Yoshihiro Sakoda; Mai Quynh Le; Hiroshi Kida; Kazumasa Ogasawara; et al. (npj Vaccines)
Abstract Outbreaks of H5 highly pathogenic avian influenza A viruses (HPAIVs) in animals pose a threat to humans immunologically naïve to avian influenza viruses. However, annual vaccination, such as for seasonal influenza is not planned because the number of human patients infected with H5 HPAIVs is small, and the possibility of human-to-human transmission of H5 HPAIVs is low at present. However, various clades of H5 HPAIVs have emerged continuously. Therefore, a vaccine that confers long-term and cross-clade immunity is required. To examine the long-term effectiveness and cross-clade reactivity of an H5 influenza virus vaccine, cynomolgus macaques were infected with an H5N1 HPAIV 5 years after two subcutaneous vaccinations with inactivated H5N1 whole-virus particles (H5 clade classical/outlier), which showed higher immunogenicity than did split vaccines in our previous studies. Neutralization titers against the vaccine strain were maintained for 5 years, and a recall immune response was observed on challenge infection against the challenge strain (clade 1) and other H5N1 HPAIV strains (clades 2.2, 2.3.2.1, and 2.3.4.4b). Compared with unvaccinated macaques, viral titers were low, and the cytokine signaling pathways related to the pathogenesis of an influenza virus infection were not activated in the vaccinated macaques. Thus, a whole-virus particle vaccine induced long-term memory sufficient to prevent severe pneumonia caused by an H5N1 HPAIV in cynomolgus macaques.